EFEKTIVITAS MEDIA VIDEO TERHADAP PENGETAHUAN PENCEGAHAN SEKS BEBAS PADA SISWA SMP NEGERI 22 PEKANBARU - Syofhia Nofri Rahmadini; Ani Triana; Juli Selvi Yanti (JOMIS (Journal of Midwifery Science), 2026)
Risky sexual behavior among adolescents remains a reproductive health concern that requires effective preventive educational interventions. Limited knowledge regarding reproductive health may increase adolescents' vulnerability to engaging in free-sex behavior. Video-based education is considered an effective medium because it delivers information through integrated visual and auditory elements. This study aimed to determine the effectiveness of video media in improving students’ knowledge regarding the prevention of free-sex behavior at SMP Negeri 22 Pekanbaru in 2026. A quantitative study with a One Group Pretest-Posttest design was conducted. The population consisted of 609 students in grades VII and VIII, with 86 respondents selected using Cluster Random Sampling. Data were collected using a knowledge questionnaire that had been tested for validity and reliability (Cronbach’s Alpha = 0.700). The intervention consisted of a 3-minute and 16-second educational video developed based on theories related to free-sex behavior. Data were analyzed using the Wilcoxon Signed Rank Test with a 95% confidence level (α=0.05). The results showed that the mean knowledge score increased from 10.05 before the intervention to 11.58 after the intervention. Statistical analysis indicated a significant effect of video media on students’ knowledge improvement (p<0.001). Video-based education was proven effective in increasing students’ knowledge regarding the prevention of free-sex behavior and may be considered an alternative reproductive health education medium in school settings.